Study of surface acoustic wave scattering and diffraction by scanning acoustic force microscopy - Hesjedal, T; Seidel, W (2002)
Scanning Acoustic Force Microscopy (SAFM) has been used to study scattering and diffraction phenomena of SAWs (surface acoustic waves) with a spatial resolution on the nanoscale. With other acoustic imaging methods, it has been difficult to achieve both nanometer lateral resolution and sub-Å wave amplitude detection sensitivity at the same time. With SAFM, amplitude distribution and phase velocity of arbitrarily polarized modes are accessible on the nanoscale. We present a model of the SAFM contrast formation and give some examples for simple experimental situations. SAW excitation by a single SAW source and the wavefield distribution within an acoustic charge transport structure are examined.